The reserve and confidentiality in the medical relationship as a manifestation of the constitutional right to privacy - Almonacid Flores, Carlos Alberto (2019)
The right to confidentiality of the medical relationship as a manifestation of the constitutional right to privacy has not merited sufficient treatment in the country. That is why in this article we try to explain the nature of this right and the place it occupies in the health system. In that sense, its main characteristics, its exceptions are outlined, highlighting three of them, and the challenges it has in the country.